Optimizing Connections: Applied Shortest Path Algorithms for MANETs - Alameri, Ibrahim Ahmed Salman; Komárková, Jitka; Al-Hadhrami, Tawfik; Yahya, Abdulsamad Ebrahim; Gharbi, Atef (Tech science press, 2024)
This study is trying to address the critical need for efficient routing in Mobile Ad Hoc Networks (MANETs) from dynamic topologies that pose great challenges because of the mobility of nodes. The main objective was to delve into and refine the application of the Dijkstra's algorithm in this context, a method conventionally esteemed for its efficiency in static networks. Thus, this paper has carried out a comparative theoretical analysis with the BellmanFord algorithm, considering adaptation to the dynamic network conditions that are typical for MANETs. This paper has shown through detailed algorithmic analysis that Dijkstra's algorithm, when adapted for dynamic updates, yields a very workable solution to the problem of real-time routing in MANETs. The results indicate that with these changes, Dijkstra's algorithm performs much better computationally and 30% better in routing optimization than Bellman-Ford when working with configurations of sparse networks. The theoretical framework adapted, with the adaptation of the Dijkstra's algorithm for dynamically changing network topologies, is novel in this work and quite different from any traditional application. The adaptation should offer more efficient routing and less computational overhead, most apt in the limited resource environment of MANETs. Thus, from these findings, one may derive a conclusion that the proposed version of Dijkstra's algorithm is the best and most feasible choice of the routing protocol for MANETs given all pertinent key performance and resource consumption indicators and further that the proposed method offers a marked improvement over traditional methods. This paper, therefore, operationalizes the theoretical model into practical scenarios and also further research with empirical simulations to understand more about its operational effectiveness.
Optimalizace připojení: Využití algoritmů nejkratší cesty pro sítě MANET
Keywords: Dijkstra's algorithm optimization; complexity analysis; shortest path first; comparative algorithm analysis; nondeterministic polynomial (NP)-complete; Optimalizace Dijkstrova algoritmu; analýza složitosti; nejkratší cesta jako první; srovnávací analýza algoritmů; nedeterministický polynom (NP)-úplný